Clinical practice guideline for the screening of colorectal cancer-2015 (2015)
Objective: To provide an evidence-based clinical practice guideline for the screening of colon and rectal cancer for patients, caregivers, administrative and government bodies at all levels of care in Colombia. Materials and Methods: This guide was developed by a multidisciplinary team with the support of the Colombian Association of Gastroenterology, Cochrane STI Group and Clinical Research Institute of the Universidad Nacional de Colombia. Relevant clinical questions were developed and the search for national and international guidelines in databases was performed. Existing guidelines were evaluated for quality and applicability. None of the guidelines met the criteria for adaptation, so the group decided to develop a de novo guideline. Systematic literature searches were conducted by the Cochrane Group. The tables of evidence and recommendations were made based on the GRADE methodology. The recommendations of the guide were socialized in a meeting of experts with government agencies and patients. Results: An evidence-based Clinical Practice Guidelines for the screening of colorectal cancer was developed for the Colombian context. Conclusions: The opportune detection of colon cancer would have an impact of the disease in Colombia. © 2015 Asociaciones Colombianas de Gastroenterología, Endoscopia digestiva, Coloproctología y Hepatología.